PENGECEKAN DAN PEMBAYARAN BARANG BERBASIS DESKTOP DI DAPUR PP EL-BAYAN CILACAP - ferdian, mohammad (Jurnal Teknologi dan Bisnis, 2021)
PP EL-Bayan Public Kitchen is a business entity owned by a pesantren that provides daily needs for students. such as boarding houses, toiletries, and others. This Public Kitchen every day carries out sales and purchases of goods within the agency. However, in managing sales and purchase transaction data at this business entity, there are still some obstacles in transaction information, for example, making sales and purchase transaction reports which are still manual. So it is proposed to create a new system for the agency, namely by making an information system for checking and paying for desktop-based goods at the PP El-bayan public kitchen using Visual Basic applications and a database system (Mysql). The purpose of this research is to assist and facilitate service operations, reporting efficiently, quickly, and accurately. In collecting data, this research uses two methods, namely the interview method, the observation method. In making the system in this study using the waterfall method, namely analysis, design, coding, and testing, and several tools such as Visual Basic, MySQL. The results obtained are a desktop-based checking and payment information system that presents data in an integrated manner